"Recognizing the Commencement of Ramadan … ": U.S. Congressional Resolutions on Ramadan, 2001–2020. Issue 1 (2nd January 2022) - Stanton, Andrea L.
Abstract: This article traces the history of the simple resolutions introduced in the United States Congress almost annually since 2001 to recognize the commencement of Ramadan, and to offer good wishes to Muslims in the United States and globally. Only one of these has passed. These symbolic resolutions have been little studied, in contrast to media attention on White House iftars and presidential Ramadan greetings. Using Congressional sources, this article argues that these symbolic resolutions, despite their limited success, offer an important lens for understanding a post-9/11 Congressional effort to recognize Muslims as an American religious minority community. The impact of these Ramadan resolutions lies in their attempt to grant national recognition to a minority religious community—an effort that has been both inclusive and contentious. Overall, Congressional resolutions and debates offer a fruitful source for scholarship on American Muslims and other religious minorities in the contemporary United States.